Economics / Third Edition - Matthews Kent; Parkin Michael; Powell Melanie (Addison-Wesley, 1997)
A highly successful text that has established itself as a market leader around the globe. Introduction, What is Economics?, Making and Using Graphs, Production and Growth and Trade, Demand and Supply, Elasticity, Markets in Action, Markets for Goods and Services, Utility and Demand, Possibilities and Preferences and Choices, Organizing Production, Output and Costs, Competition, Monopoly, Monopolistic Competition and Oligopoly, Markets for Factors of Production, Pricing and Allocating Factors of Production, Labor Markets, Capital and Natural Resource Markets, Uncertainty and Information, Markets and Governments, Market Failure and Public Choice, Regulation and Privatization, Externalities and the Environment and Knowledge, Inequality and Redistribution and Welfare, Preliminaries and Long-Term Fundamentals, Employment and Unemployment and Wages, Investment and Capital and Interest, Long Term Economic Growth, Macroeconomic Fluctuations and Policies, Aggregate Supply and Aggregate Demand, Expenditure Multipliers, Money, The Global Economy, Glossary, Index.